2004
DOI: 10.1158/0008-5472.can-04-1330
|View full text |Cite
|
Sign up to set email alerts
|

HOXB13 Induces Growth Suppression of Prostate Cancer Cells as a Repressor of Hormone-Activated Androgen Receptor Signaling

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
132
2
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 50 publications
9
132
2
2
Order By: Relevance
“…HOXB13 methylation is associated with gene silencing Although abundant expression of HOXB13 in normal prostate and colorectal tissues of adult mouse and humans has been reported (Sreenath et al, 1999;Jung et al, 2004b), our reverse transcription-PCR (RT-PCR) analysis revealed that HOXB13 is also expressed in the normal human kidney, testis, uterus, placenta, and thymus in addition to the prostate (Figure 3a). To elucidate whether aberrant methylation of HOXB13 is associated with the loss of its expression in RCCs, we analysed the expression of HOXB13 in 15 RCC lines by RT-PCR that amplified the HOXB13 cDNA to plateau levels ( Figure 3b).…”
Section: Resultsmentioning
confidence: 88%
“…HOXB13 methylation is associated with gene silencing Although abundant expression of HOXB13 in normal prostate and colorectal tissues of adult mouse and humans has been reported (Sreenath et al, 1999;Jung et al, 2004b), our reverse transcription-PCR (RT-PCR) analysis revealed that HOXB13 is also expressed in the normal human kidney, testis, uterus, placenta, and thymus in addition to the prostate (Figure 3a). To elucidate whether aberrant methylation of HOXB13 is associated with the loss of its expression in RCCs, we analysed the expression of HOXB13 in 15 RCC lines by RT-PCR that amplified the HOXB13 cDNA to plateau levels ( Figure 3b).…”
Section: Resultsmentioning
confidence: 88%
“…In contrast, overexpression of HOXB13 in prostate cancer cells resulted in inhibition of cell growth and suppression of hormone-activated androgen receptor transcriptional activity, presumably via physical interaction with the receptor [24,25]. In the same study it was seen that estradiol-stimulated ER activity in breast cancer cells was not suppressed by HOXB13; in fact, if there was any influence on the activity it appears as though HOXB13 enhanced this activity [25]. Recent studies on ER signaling suggests HOXB13 to be an ER target gene since its expression in breast cancer cells is suppressed after estrogen stimulation [26].…”
Section: Discussionmentioning
confidence: 94%
“…In human cutaneous malignant melanoma with distant metastasis, the expression level of certain HOX genes, including HOXB13, was higher than in those melanoma patients without metastases [23], and in endometrial cancer cells, antisense-transfection of the HOXB13 gene reduced the invasive ability of the cells [19]. In contrast, overexpression of HOXB13 in prostate cancer cells resulted in inhibition of cell growth and suppression of hormone-activated androgen receptor transcriptional activity, presumably via physical interaction with the receptor [24,25]. In the same study it was seen that estradiol-stimulated ER activity in breast cancer cells was not suppressed by HOXB13; in fact, if there was any influence on the activity it appears as though HOXB13 enhanced this activity [25].…”
Section: Discussionmentioning
confidence: 99%
“…Embryos were staged by assigning noon of the day of vaginal plug as E0. 5 (42). DNA template was linearized and DIG labeled antisense probes were prepared by in vitro transcription with SP6, T3 or T7 polymerase (Roche).…”
Section: Methodsmentioning
confidence: 99%
“…Loss of Hoxc6 expression can induce apoptosis in prostate cancer cells (4), and Hoxb13 is a repressor of hormone-activated androgen receptor inducing growth suppression of prostate cancer cells (5,6). Hoxb7 is a key factor for a tumor-associated angiogenic switch shown to activate basic fibroblast growth factor that in turn promotes cellular proliferation (7).…”
mentioning
confidence: 99%